EVALUASI STRATEGI KEUNGGULAN BERSAING PGN DI BIDANG USAHA HILIR GAS BUMI - , Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The business environment continues to change. This change makes business management to become increasingly complex. Companies that are not able to adapt to change will not be able to produce reliable performance and result in waning competitiveness and reputation of the company. PGN as a state-owned company before the issuance of oil and gas law of 2001 is a single player in the natural gas distribution business conditions of free competition must confront the threats that erode the market share of competitors that have long dominated. Appropriate strategies are necessary to sustain competitive advantage. For that, analysis of the environmental situation of 5 industrial strengths and what factors determine PGN competitive advantage through a SWOT analysis need to be conducted. The results obtained PGNâs position in grow and build strategies for market penetration, market development and business activities that lead to patterns of integration along the gas value chain business in order to ensure adequate drainage of gas consumers.